Les espaces ruraux du Brahmapoutre et les villes d’Assam : des chemins divergents ? - Émilie Cremin; Annick Hollé (EchoGéo)
In northeast India, economic growth disproportionally benefits certain populations living within the Brahmaputra flood plain. The river itself is at once a longitudinal link across the State of Assam, and a medium-scale break separating villages and cities. Its’ dramatic rise and fall, prompted by the annual monsoon rainfall, can cause fearsome flooding. Even when the river is controlled through embankments, inundations can inundate and destroy entire villages and rural areas. Local institutions in charge of implementing land management schemes put into place by the central government are failing to mitigate the precarious conditions in rural areas. At the same time, the use of modern means of telecommunication is increasingly popular in rural areas. However, only local elites, rather than common people, have effective access to the Internet in urban areas. The privileged few can also take airplanes connecting them to capital cities within a few hours, while at the socio-economical gap between urban and rural citizens continues to widen.